Synonymy, redescription, molecular characterisation, and new distribution data of species of Stilestrongylus and Guerrerostrongylus (Nematoda, Heligmonellidae) parasitic in sigmodontine rodents from Argentina and Uruguay: a collection-based survey - Digiani, Maria Celina (2024)
In this study, we review the taxonomic status of the parasitic nematodes Stilestrongylus oryzomysi and Guerrerostrongylus uruguayensis (Heligmonellidae), which had been described only once from sigmodontine rodents from Argentina and Uruguay, respectively. To this aim, we examined 38 complete helminth sets deposited in the Helminthological Collection of the Museo de La Plata (MLPHe), Argentina, including type material of G. uruguayensis, S. oryzomysi, and a closely related species, Stilestrongylus azarai. We also examined voucher rodent specimens deposited in the Mammal Collection of the Museo de La Plata (MLP-Mz) to assess the identity of the symbiotypes and other rodent hosts. Based on these observations, S. oryzomysi is proposed as a junior synonym of S. azarai; the identity of the symbiotype of S. oryzomysi and Trichofreitasia lenti (Heligmonellidae) is emended from Oligoryzomys flavescens to Akodon azarae; G. uruguayensis is proposed as a junior synonym of Guerrerostrongylus zeta; S. azarai is redescribed based on type and voucher material; and the latter species and G. zeta are molecularly characterised using the ITS+ gene. We extend the geographic distribution of S. azarai to include Uruguay and provide a new host record for T. lenti (A. azarae, type host species), a new host record for G. zeta in Argentina (O. flavescens), and the first record of helminths for Oligoryzomys nigripes in Uruguay.